Cardiovascular effects of incretin-based therapies in patients with type 2 diabetes: a systematic review and network meta-analysis. (November 2016) - Wu, Shanshan; Yang, Jun; Cai, Ting; Xu, Yang; Yang, Zhirong; Zhang, Yuan; Chai, Sanbao; Sun, Feng; Zhan, Siyan
Abstract: Background: Concerns about the cardiovascular safety of incretin-based therapies, which include dipeptidyl peptidase-4 inhibitors and glucagon-like peptide-1 receptor agonists, in patients with type 2 diabetes have been raised. We aimed to systematically assess the cardiovascular effects of incretin-based therapies in patients with type 2 diabetes. Methods: In this systematic review and network meta-analysis, we searched MEDLINE, Embase, the Cochrane library, andClinicalTrials.gov from inception to April 28, 2016, for reports of randomised controlled trials. We included reports with available data comparing incretin-based therapies with placebo and traditional antidiabetic drugs in patients with type 2 diabetes, with a minimum follow-up period of 12 weeks, and we extracted data from these reports. The main outcome was a composite of major adverse cardiovascular events (including cardiovascular death, myocardial infarction, and stroke, as defined by the US Food and Drug Administration) and heart failure. We used a random-effects model to calculate odds ratios (ORs) with 95% CI, and did a network meta-analysis to supplement direct comparisons. This study is registered with PROSPERO, number CRD42015020395. Findings: Of 4873 trials identified in the search, 271 trials with eight treatments (incretin-based therapies, placebo, and six traditional antidiabetic drugs—metformin, insulin, sulfonylureas, thiazolidinediones, alpha-glucosidase inhibitors, and sodium-glucose co-transporter 2 inhibitors) and 162 729 patients were included in analysis. In pairwise meta-analysis, incretin-based therapies had a significantly decreased risk of cardiovascular events compared with placebo (OR 0·75, 95% CI 0·64–0·87) and sulfonylureas (0·78, 0·61–0·98). However, in network meta-analysis, the protective effect of incretin-based therapies on cardiovascular events was not detected compared with placebo (0·94, 0·87–1·02) and was evident only compared with sulfonylureas (0·77, 0·61–0·98). Incretin-based therapies did not have an increased cardiovascular risk compared with other traditional antidiabetic drugs in both pairwise and network meta-analyses. Ranking probability analysis showed that incretin-based therapies had the lowest cardiovascular risk among all eight treatments with a probability of 67·5%, followed by alpha-glucosidase inhibitors (65·2%) and sodium-glucose co-transporter 2 inhibitors (61·3%). Interpretation: Incretin-based therapies seems to be associated with a decreased cardiovascular risk compared with placebo and sulfonylurea, and did not show any increased risk of cardiovascular events compared with other traditional antidiabetic drugs. Funding: National Natural Science Foundation of China (81302508).